Studi Tentang Kesesuaian Lahan Untuk Tanaman Kelapa Sawit (Elaeis Guineensis Jacq) Di Kecamatan Kinali Kabupaten Pasaman Barat - Ayusni, Ayusni; Hermon, Dedi; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This research aimed to know the land characteristic for the plantation of palm (elevation, elongation, effective depth, drainage, texture, soil acidity, soil salinity, rainy rate, temperature, rock surface, dept rock layer, cation of soil) on each the form of existing area at the Kinali district of West Pasaman Regency. The unity of form of existing area which is observed consisted of six units of land form and the sample for this research was just five units of land form.Technique of taking the sample was random sampling strategy that is a technique of taking sample by using strata of land form. The analysis of data in this research used descriptive analysis, it an analysis of contrastive tables between land characteristic (elevation, elongation, effective depth, drainage, texture, soil acidity, soil salinity, rainy rate, temperature, rock surface, cation of soil) compared with the feasibility level of the land for the plantation of palm.The result of research showed that: 1) there were support factors and barrier factors. Some support factors are: temperature, texture of soil, elevation, surface of rock, dept rock layer, soil acidity and cation of soil) while the barrier factors are rainy rate, drainage, curve elongation and salinity). 2) there were a feasibility level of the land for the plantation of palm at Kinali District showed that the level of the land came into feasible category to plant the palm which occupied in the form unit of the land, those are, Fluvial layer, Volcanic line, volcanic hill, under and middle elongation ofÂ  mountain area.